2019
DOI: 10.1021/acs.joc.9b02010
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic Halogenation of Cyclic Nitronates: A General Access to 3-Halo-1,2-Oxazines

Abstract: In this article, comprehensive studies on the nucleophilic chlorination and bromination of readily available six-membered cyclic nitronates (1,2-oxazine-N-oxides) are reported. Under optimized conditions (POCl3 or (COBr)2 with Hünig’s base), 3-halo-substituted 1,2-oxazines, which are difficult to access by other routes, were obtained in good to high yields. The latter were shown to be convenient precursors to other 3-substituted 1,2-oxazine derivatives using Lewis/Brønsted acid-assisted substitution of the ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Recently our group [70] developed a general method for the synthesis of 3‐halosubstituted 1,2‐oxazines 45 and 46 via nucleophilic halogenation of corresponding N ‐oxides 44 (Scheme 17). Nucleophilic chlorination was readily accomplished with POCl 3 / i Pr 2 NEt in DMF at 0 °C, although SOCl 2 and oxalyl chloride could be used with nearly the same efficiency (Scheme 17, a).…”
Section: Non‐aromatic Heterocyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently our group [70] developed a general method for the synthesis of 3‐halosubstituted 1,2‐oxazines 45 and 46 via nucleophilic halogenation of corresponding N ‐oxides 44 (Scheme 17). Nucleophilic chlorination was readily accomplished with POCl 3 / i Pr 2 NEt in DMF at 0 °C, although SOCl 2 and oxalyl chloride could be used with nearly the same efficiency (Scheme 17, a).…”
Section: Non‐aromatic Heterocyclesmentioning
confidence: 99%
“…The resulting halides 45 and 46 were used to prepare challenging 3‐substituted 1,2‐oxazines [73] and tetrazolo[1,5‐b][1,2]oxazines by acid‐assisted nucleophilic substitution of the halogen atom (Scheme 18). [70] …”
Section: Non‐aromatic Heterocyclesmentioning
confidence: 99%
“…The solution containing sodium or ammonium chloride acted as the halogen source. It was also observed that mono chlorination occurred when NH 4 Cl solution was used instead of NaCl. The halogenated products (10)/(10 a) were obtained in high yields (Scheme 4).…”
Section: Chlorinationmentioning
confidence: 99%
“…[ 2 ] Different functionalities have been incorporated via ‘C‐halogenated’ positions giving rise to a broad range of interesting products [3] . Some interesting C−H bond halogenation have been observed in different molecules [4–7] . Various approaches have been made to insert suitable halogen regioselectively at desired position of a particular organic moiety with high enantioselectivity [1c] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation